Exponential Inequalities for Positive Linear Mappings - Mohammad Sababheh; Hamid Reza Moradi; Shigeru Furuichi (Journal of Function Spaces)
In this article, we present exponential-type inequalities for positive linear mappings and Hilbert space operators, by means of convexity and the Mond-Pečarić method. The obtained results refine and generalize some known results. As an application, we present extensions for operator-like geometric and harmonic means inequalities.